Pengaruh model bisnis, inovasi produk dan literasi keuangan terhadap kelangsungan usaha kecil menengah menuju UKM Bangkit dari Pandemi Covid-19 - Dina Ekasari, Luh; Sularsih, Hermi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The purpose of this study is to determine the influence of business models, product innovation and financial literacy towards sustaining small and medium enterprises to SMEs to rise from the Covid 19 pandemic. The population in this study is MSMEs registered with the Office of Cooperatives and Micro Enterprises in Malang City. While the sample used in this study were 119 respondents with the data collection method using the survey method, namely the primary data collection technique obtained directly in the form of opinions or opinions from the subjects studied (respondents) by answering stand-questionnaire statements as measured by a Likert scale. which will be processed using SPSS data analysis techniques. The results of this study are that the variables business model, product innovation, financial literacy have a positive effect on the variable maintaining small and medium businesses rising from the covid 19 pandemic